Nominalization in languages of the Americas - Zariquiey, Roberto; Shibatani, Masayoshi; Fleck, David W. (David William), 1969- (Typological studies in language, 2019)
"Recent scholarship has confirmed earlier observations that nominalization plays a crucial role in the formation of complex constructions in the world's languages. Grammatical nominalizations are one of the most salient and widespread features of languages of the Americas, yet they have not been approached as foundational grammatical structures for constructions such as relative clauses and complement clauses. This is due to an imbalance in past scholarship, which has tended to focus on these constructions at the expense of the nominalization structures underlying them. The papers in this collection treat grammatical nominalizations in their own right, and as a starting point for the investigation of their uses in complex grammatical structures. A representative sample of Amerindian languages, with focus on South America, examines properties of grammatical nominalizations such as their multiple functions, their internal and external syntax, and their diachronic development. Among the far-reaching theoretical conclusions reached by the studies in this volume is that the various types of relative clauses recognized in the typological literature are actually no more than epiphenomena arising from the different uses of grammatical nominalizations"--